1997
DOI: 10.1017/s0953756296003358
|View full text |Cite
|
Sign up to set email alerts
|

Comparative determination of cerato-ulmin on cell surface and in mycelial extracts of pathogenic and non-pathogenic Ophiostoma species

Abstract: Cerato-ulmin (CU) presence was monitored on cell surface and quantitatively determined in mycelial extracts of the elm pathogens Ophiostoma novo-ulmi (races EAN and NAN) and O. ulmi and of the non-pathogenic O. piceae. CU was detected on the surfaces of Ophiostoma novo-ulmi (races EAN and NAN) and, for the first time, of the weak Dutch elm disease pathogen O. ulmi and the nonpathogen O. piceae. Quantitative determination of CU content in the mycelial extracts of the three species showed that high CU cellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…CU is known to be produced by these pathogens at different levels in liquid cultures (Scheffer et al 1987). Besides being secreted in cultures, CU is also found in the cell wall, on the cell surface and in mycelial extracts of O. novo -ulmi and O. ulmi (Takai and Hiratsuka 1980;Svircev et al 1988;Scala et al 1997). It has been hypothesized that the expression of the single copy cu gene coding for this protein is controlled at the level of transcription (Jeng et al 1996;Pipe et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CU is known to be produced by these pathogens at different levels in liquid cultures (Scheffer et al 1987). Besides being secreted in cultures, CU is also found in the cell wall, on the cell surface and in mycelial extracts of O. novo -ulmi and O. ulmi (Takai and Hiratsuka 1980;Svircev et al 1988;Scala et al 1997). It has been hypothesized that the expression of the single copy cu gene coding for this protein is controlled at the level of transcription (Jeng et al 1996;Pipe et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the abundant secretion of cerato-ulmin during pathogenesis and its indirect role in pathogenicity. O. ulmi and O. novo-ulmi are dimorphic fungi that are capable of growing as either yeast or mycelium, and CU is produced in both developmental stages (Takai and Hiratuska 1980;Puhalla and Bell 1981;Scala et al 1997). The data produced to date would suggest that the yeastlike stage is involved in disease dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…No explanation is as yet available for this observation, even if Scala et al (1997) suggested that it could depend on differences in the regulation of CU synthesis and in sorting and secretion mechanisms between the Ophiostoma species.…”
Section: Analysis Of the Deduced Geo1 Proteins In Geosmithia Speciesmentioning
confidence: 94%
“…Also species in the genus Ophiostoma showed a different behaviour with respect to the secretion of the class II hydrophobin cerato-ulmin (CU) in the culture medium: Ophiostoma novo-ulmi and Ophiostoma himal-ulmi secreted high amounts of CU, Ophiostoma ulmi nil or low amount, while no CU was detected in Ophiostoma quercus culture medium (Brasier & Mehrotra 1995;Scala et al 1997). No explanation is as yet available for this observation, even if Scala et al (1997) suggested that it could depend on differences in the regulation of CU synthesis and in sorting and secretion mechanisms between the Ophiostoma species.…”
Section: Analysis Of the Deduced Geo1 Proteins In Geosmithia Speciesmentioning
confidence: 99%
“…Cerato-ulmin (CU) is a class II hydrophobin of about 8 kDa present on the cell surface and/or excreted in culture by the phytopathogenic fungi Ophiostoma ulmi, O. novo-ulmi, and Ophiostoma himal-ulmi, and by the nonpathogen Ophiostoma quercus (Svircev et al 1988;Scala et al 1997;Carresi et al 2008). Ophiostoma ulmi and O. novo-ulmi are responsible, respectively, for the first and the second DED pandemics that decimated elm populations in Europe, North America, and Asia since the last century.…”
Section: Introductionmentioning
confidence: 99%